Bone Healing by Using Ilizarov External Fixation Combined with Flexible Intramedullary Nailing versus Ilizarov External Fixation Alone in the Repair of Tibial Shaft Fractures: Experimental Study - A. V. Popkov; N. A. Kononovich; E. N. Gorbach; S. I. Tverdokhlebov; Y. M. Irianov; D. A. Popkov (The Scientific World Journal)
Purpose. Our research was aimed at studying the radiographic and histological outcomes of using flexible intramedullary nailing (FIN) combined with Ilizarov external fixation (IEF) versus Ilizarov external fixation alone on a canine model of an open tibial shaft fracture. Materials and Methods. Transverse diaphyseal tibial fractures were modelled in twenty dogs. Fractures in the dogs of group 1 (n=10) were stabilized with the Ilizarov apparatus while it was combined with FIN in group 2 (n=10). Results. On day 14, a bone tissue envelope started developing round the FIN wires. Histologically, we revealed only endosteal bone union in group 1 while in group 2 the radiographs revealed complete bone union on day 28. At the same time-point, the areas of cancellous and mature lamellar bone tissues were observed in the intermediary area in group 2. The periosteal layers were formed of the trabeculae net of lamellar structure and united the bone fragments. The frame was removed at 30 days after the fracture in group 2 and after 45 days in group 1 according to bone regeneration. Conclusion. The combination of the Ilizarov apparatus and FIN accelerates bone repair and augments stabilization of tibial shaft fractures as compared with the use of the Ilizarov fixation alone.